Analisis Kinerja Ruas Jalan Pada Bundaran Simpang Enam Tugu Merah (Study Kasus : Km.24, Aimas, Sorong, Papua Barat Daya) - Saifudin, Ahmad; Rahmat, Andi; Syara, Elfiyusriningsi (CV. Shofanah Media Berkah, 2025)
Sorong City as one of The cities in the eastern Indonesian region that is actively implementing the expansion and equalization of economic activity areas. This condition has an impact on the very high need for transportation in Sorong City. According to the BPS of Sorong Regency from 2020-2023 the population in Aimas District was 42,014 people, 43,954 people, 46,195 people and 48,499 people, while the number of vehicles in Sorong City from 2017-2021, amounted to 107,285 units, 115,502 units, 123,723 units, 129,514 units and 135,403 units. (BPS Sorong City). From the BPS data, it can be concluded that the number of vehicles and residents of Sorong City will continue to increase every year, of course the need for transportation will also increase, therefore this research needs to be done to support adequate transportation needs.